Criminal Law Policy in Dealing With The Development of Transnational Cyber Crime - Saptha Nugraha Isa; Rahmayanti Rahmayanti; Paulus Purba; Krismanto Manurung (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2025)
This abstract analyzes the urgency of criminal law policy in tackling the rapidly evolving transnational cybercrime. The rapid advancement of information and communication technology has created increasingly complex, cross-border, and difficult-to-detect cybercrime modus operandi. Indonesia, as part of the global community, faces serious challenges in formulating and implementing effective regulations to combat these crimes. This research aims to identify the challenges of criminal law in Indonesia in dealing with transnational cybercrime and to formulate adaptive strategies to strengthen the existing legal framework. Normative-empirical research methods are employed with a case study approach, legislative analysis, and international legal comparison. The findings indicate that the harmonization of national laws with international standards, enhancement of law enforcement capacity, and strengthening of inter-state cooperation are key. Innovation in criminal law approaches is also needed, focusing not only on prosecution but also on prevention and recovery of losses. The conclusion of this study emphasizes the necessity of comprehensive reform in criminal law policy, encompassing substantive, procedural, and institutional aspects, to create a system responsive to the dynamics of transnational cybercrime.